Deepfakes and Manipulative Linguistics in the Viralization of Speech Videos: A Critical Discourse Analysis of Digital Media Dynamics in 2025 - Alfi Chasanah; Asngadi Rofiq (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Deepfake, or artificial intelligence-based media synthesis technology, is capable of manipulating or generating realistic images and voices of individuals in video and audio formats. This study aims to examine how deepfake technology is combined with manipulative linguistic strategies in the process of viralizing speech videos in digital media in 2025. The research focuses on revealing how manipulative discourse is constructed through deepfake audio-visual features and persuasive language choices, and how audiences interpret and repost it. This study uses a descriptive qualitative approach with a multimodal Critical Discourse Analysis (CDA) method. The research data consists of viral deepfake videos of public figures' speeches along with captions, titles, and user comments on TikTok, X (Twitter), YouTube, and WhatsApp platforms. Data collection techniques were carried out through non-participatory observation and documentation, while data analysis included the stages of reduction, presentation, and data verification. The results of the study show that deepfakes are used to build false credibility through visual similarities, audio manipulation, and situational contexts that are familiar to the audience.  The dominant manipulative linguistic techniques include presuppositions, dichotomous lexicalization, high modalization, emotional framing, and the use of metaphors that reinforce the polarization of meaning. In addition, a symbiotic relationship was found between deepfake technology, discourse strategies, and platform algorithms that accelerate viralization and shape rhetorical hyper-realities in the digital public sphere. This study concludes that manipulative discourse in deepfake videos not only represents a false reality, but also actively shapes public opinion and power relations in digital media. Therefore, this study emphasizes the importance of strengthening critical media literacy, developing ecosystem-based risk policies, and designing technology oriented towards discourse safety in facing the dynamics of future digital media.